2021
DOI: 10.3389/fpsyt.2021.797601
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Suicide in the Context of COVID-19: Evidence From Three Australian States

Abstract: Aims: We aimed to determine whether there has been a change in the number of suicides occurring in three Australian states overall, and in age and sex subgroups, since the COVID-19 pandemic began, and to see if certain risk factors for suicide have become more prominent as likely underlying contributing factors for suicide.Method: Using real-time data from three state-based suicide registers, we ran multiple unadjusted and adjusted interrupted time series analyses to see if trends in monthly suicide counts cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…A national surveillance showed that 10.7% responders had severe suicide ideation in the past month, and the phenomenon was significantly more prominent in female patients, minority population, unpaid caregivers, and essential workers [ 21 ]. Furthermore, unemployment during the pandemic may be related to an increased suicide rate [ 22 ]. Although no clear evidence is available to determine psychosocial factors directly contributing to their distress, younger people and women may be the most vulnerable with low financial support during the pandemic because of the social disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…A national surveillance showed that 10.7% responders had severe suicide ideation in the past month, and the phenomenon was significantly more prominent in female patients, minority population, unpaid caregivers, and essential workers [ 21 ]. Furthermore, unemployment during the pandemic may be related to an increased suicide rate [ 22 ]. Although no clear evidence is available to determine psychosocial factors directly contributing to their distress, younger people and women may be the most vulnerable with low financial support during the pandemic because of the social disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal study only included four months of lockdown, had a small population (n=1,241) and participants were only aged 9-16 years which could, together with differences in the lockdowns, explain why the findings differ from ours even though the methodology is very similar. We were not able to include suicides from the cause-of-death register to explore the potential increase in suicide among especially young women as suggested by preliminary unvalidated Danish data and current international literature [15][16][17][18] . Regarding EDs, previous studies used data on new ED diagnosis or hospital admissions which increased during lockdown contrary to our findings [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…An international register-based study including pre-liminary suicide data from 21 countries in all age groups, showed no evidence of increased suicide rates during the first year of the pandemic 15 . However, other studies have suggested increased suicide rates during lockdown when including young people only and pre-liminary and unvalidated data based on Danish registers reviled a signal of an increased number of suicides among young women aged 20-24 years [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…So zeigte sich beispielsweise in Studien aus Japan [ 25 ], dass es nach einem Rückgang der Suizidzahlen im Rahmen der ersten Infektionswelle (Februar bis Juni 2020) zu einer deutlichen Zunahme der Suizidzahlen im Rahmen der zweiten Infektionswelle (Juli bis Oktober 2020) gekommen ist [ 26 ] – besonders prononciert war dieser Zuwachs bei (Haus-)Frauen, Kindern und Jugendlichen [ 27 ]. Differenzielle Effekte zeigten sich auch in anderen Studien, so fanden sich beispielsweise Hinweise darauf, dass Suizide in Maryland insbesondere unter Afroamerikanern [ 28 ] und in Australien bei jungen Männern (< 25 Jahre; [ 29 ]) zugenommen haben. Hinter den Gesamtzahlen verbergen sich somit potenzielle Unterschiede zwischen demografischen Gruppen und/oder geografischen Gebieten.…”
Section: Suizide Im Rahmen Der Pandemieunclassified